Editorial for the Special Issue on State-of-the-Art CMOS and MEMS Devices - Zhiming Chen (Micromachines, 2024)
Complementary Metal Oxide Semiconductor (CMOS) and Micro-Electro-Mechanical System (MEMS) devices play significant roles in emerging research fields such as artificial intelligence (AI) [...]